Geology of ultrahigh-temperature metamorphic rocks from Tonagh Island in the Napier Complex, East Antarctica - Osanai, Yasuhito; Toyoshima, Tsuyoshi; Owada, Masaaki; Tsunogae, Toshiaki; Hokada, Tomokazu; Crowe, Warwick A. (National Institute of Polar Research, 1999)
P(論文) The summer party of the 39th Japanese Antarctic Research Expedition (1997-1998) carried out geological field work on Tonagh Island, located at the southern-end of Amundsen Bay, northern Enderby Land, which belongs to the central Napier Complex and shows part of the highest-grade metamorphic region in the Napier Complex. The island is underlain by various kinds of ultrahigh-temperature (UHT) metamorphic rocks and subordinate amounts of two types of unmetamorphosed intrusive rocks (alkali-dolerite and granitic pegmatite). UHT-metamorphic rocks are subdivided into five lithologic units (Units I to V) owing to their lithologies and geological structures from north to south, bounded by thrust-shear zones, accompanied with remarkable anhydrous mylonite and later pseudotachylite-cataclasite. The distinctive metamorphosed mafic dikes with tholeiitic composition are also found along the shear zone, characteristically at the boundary between Units II and III. The unmetamorphosed alkali-dolerite dikes, which are designated Amundsen dikes, cut across not only the sequence of metamorphic rocks but also the unit boundary shear zone and metamorphosed mafic dike. A geological perspective of the metamorphic rocks from Tonagh Island is generally classified into eight types on the regional map scale such as 1) orthopyroxene-bearing quartzofeldspathic gneiss, 2) garnet-bearing quartzofeldspathic gneiss, 3) two pyroxene-bearing mafic granulite, 4) garnet-orthopyroxene gneiss and granulite, 5) magnetite-quartz gneiss, 6) metamorphosed ultramafic rocks, 7) layered gneiss 1 (composed mainly of mafic gneiss and orthopyroxene-bearing quartzofeldspathic gneiss), 8) layered gneiss 2 (composed mainly of mafic gneiss and garnet-bearing quartzofeldspathic gneiss) with subordinate meta-impure quartzite, aluminous granulite, and calc-silicate granulite. The orthopyroxene-bearing quartzofeldspathic charnockitic gneiss and garnet-bearing quartzofeldspathic gneiss are the main constituents of Tonagh Island. Unit I has a peculiarity of ...